Prevalencia de Demodex folliculorum e Demodex brevis em uma amostra da população de Botucatu, São Paulo, Brasil - N.G. Madeira; M.I.L. Sogayar (Sociedade Brasileira de Medicina Tropical (SBMT), 1993)
Pela primeira vez no Brasil foi realizado um levantamento para se conhecer a distribuição do D. folliculorum e D. brevis no homem. Uma amostra de 100 pessoas atendida em clínica estética foi examinada, procurando-se estudar a associação entre a presença de ácaros e fatores como idade, raça e sexo do hospedeiro. O material colhido da região facial dos indivíduos foi montado em lâminas com o meio de Berlese. Das 100 pessoas examinadas, 72 % foram positivas. Dos casos positivos, 51 % estavam infestados pelo D. folliculorum, 2% pelo D. brevis e 19% apresentaram-se parasitados por ambas as espécies. A survey was conduced to determine the prevalence of D. folliculorum and D. brevis for the first time in Brazil. In this study, association between the presence of mites and hostfactors (age, sex and race) were anatysed. Samples were obtained from 100 individuals submitted to a facial cleaning in an aesthetic clinic in Botucatu city. All the samples were mounted in Berleses medium and examined by dark-field phase microscopy. From 100 studied individuais, 72 were positive, among the positive cases, 51% showed D. folliculorum, 2% showed D. brevis and 19% both species. The parasite distribution in realtion to sex was not taken in account because the sex ratio tavoured females (90%). According to age, prevalence was high in all age groups. The factors influencing this distribution could be due. 1. the examination of extensive skin areas, 2. the group examined composed of individuals in treatment in an anaesthetic clinic could be more infested than a normal population, 3. the fact that in tropics, the prevalence is often high in all ages.